2014
DOI: 10.5489/cuaj.1226
|View full text |Cite
|
Sign up to set email alerts
|

Penile fracture with bilateral corporeal rupture without urethral involvement

Abstract: Cite as: Can Urol Assoc J 2014;8(1-2):e51-3. http://dx.doi.org/10.5489/cuaj.1226 Published online January 14, 2014. AbstractConcomitant urethral injury is rare in penile fracture. We report the case of a 34-year-old male who presented to the emergency department 12 hours after a blunt self-injury of the penis. Physical examination revealed a swollen, ecchymotic, and deviated circumcised penis without blood at the meatus. The fracture line extending along the bilateral corpora without urethral involvement was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Rupture of the right, and left cavernous bodies were detected in 2 (4%) cases either without involvement of the corpus spongiosum (n=1) or associated with urethral laceration (n=1). [10] We observed blood on external meatus of 2 (4%) patients. Mucosal laceration of the urethra in 4 (7%) patients were repaired using 4/0 absorbable interrupted sutures with primary closure of firstly mucosa, and then corpus spongiosum.…”
Section: Resultsmentioning
confidence: 99%
“…Rupture of the right, and left cavernous bodies were detected in 2 (4%) cases either without involvement of the corpus spongiosum (n=1) or associated with urethral laceration (n=1). [10] We observed blood on external meatus of 2 (4%) patients. Mucosal laceration of the urethra in 4 (7%) patients were repaired using 4/0 absorbable interrupted sutures with primary closure of firstly mucosa, and then corpus spongiosum.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,5 Penile fracture with bilateral corporal laceration also indicates high-energy trauma and there are only two case reports of bilateral corporal involvement without concomitant urethral rupture. 14,15 Neither of these cases had an etiology of sexual intercourse with one caused by self-manipulation 14 and the other by blunt trauma. 15 Amit et al reported eight concomitant urethral rupture cases with one bilateral involvement with complete urethral disruption.…”
Section: Discussionmentioning
confidence: 95%
“…A PF with bilateral corporal lacerations is thought to indicate high-energy trauma. Urethral damage may also occur in the presence of bilateral corporal lacerations due to such kind of trauma [18]. In the literature, the rate of bilateral cavernosal rupture after PF is reported to range between 0% and 26.3%, while urethral damage occurs in 5.8-27.5% of cases [9,19].…”
Section: Discussionmentioning
confidence: 99%